(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The coffee house, which originated in the Middle East around 1511, began as merely a place to enjoy an exotic drink, that is, coffee, but soon evolved into a place that changed the course of history. Before coffee houses arrived in London, the normal social gathering place was a pub or a tavern. The first attraction to coffee might have been its newness or exhilaration from the caffeine, but quickly it became another reason to meet, and the coffee house became a place for socialization. This study aimed to promote the local coffee beans and delicacies of the Philippines. This study utilized a survey questionnaire of a research sample with 100 possible customers of the A Latte of Fun. This study considered the perceptions of customers toward the promotion of the local coffee beans of the Philippines. Customers have been familiar with too many coffee beans of different coffee shops that offer international coffee beans but not local coffee beans. Hence, the researchers wanted to promote the local coffee beans and delicacies of the Philippines. Based on the results of the survey, customers prefer to have a hot coffee. A total of 70% of the respondents want a hot coffee, and 76% of the respondents prefer to eat delicacies while drinking coffee. The results of the survey showed positive feedback and presented a high percentage of being purchased. The researchers promoted local coffee beans because they have health benefits to young people and adults. The researchers saw a positive outcome in promoting the local coffee bean to the surveyed customers. This study can help coffee lovers to learn about the difference in the taste of local coffee beans. This study also provided information about the perception of customers if they agreed about the proposed products, that is, the local coffee bean and delicacies of the Philippines. The researchers also wanted to know what is the preferred coffee bean of the target market in terms of the customers’ perception. This study is not only for owners but also for coffee lovers.